E-Tax Module as a Suitable Media in Accounting Learning - Nirbita, Betanika Nila; Norviana, Syahida; Jannah, Lu'lu'ul (Journal of Economics Education and Entrepreneurship, 2024)
Income Tax Reform Law Number 7 of 2021 concerning Harmonization of Tax Regulations was implemented on January 1, 2022. This means that tax material has also undergone changes. This change is not supported by the existence of effective learning media. This research aims to determine the suitability of the media that will be used in the taxation learning process. The research is research and development with 4D Models, but in this research, there are restrictions on research procedures to product feasibility tests. The media feasibility test is carried out through validation to material, language, media, and practitioners experts, initial feasibility tests and broad feasibility tests. The media feasibility test consists of material, media, language and practitioner validation tests involving various experts in their respective fields. Based on the validation results of experts (material experts, media experts, language experts and practitioner experts), the ETM teaching material media (E-Tax Module) was declared valid and suitable for use as a Taxation learning media. Apart from assessments from experts, the ETM (E-Tax Module) teaching material media was tested on students which included limited trials and extensive trials. The results of limited trials and extensive trials stated that the ETM (E-Tax Module) media was declared valid and suitable as a tax learning medium. So based on these two assessments it can be concluded that the ETM (E-Tax Module) media is declared valid and appropriate as a Taxation learning media.